The Development and Evolution of the U.S. Law of Corporate Criminal Liability - Beale, Sara Sun (2014)
In the United States, corporate criminal liability developed in response to the industrial revolution and the rise in the scope and importance of corporate activities. This article focuses principally on federal law, which bases corporate criminal liability on the respondeat superior doctrine developed in tort law. In the federal system, the formative period for the doctrine of corporate criminal liability was the early Twentieth Century, when Congress dramatically expanded the reach of federal law, responding to the unprecedented concentration of economic power in corporations and combinations of business concerns as well as new hazards to public health and safety. Both the initial development of the doctrine and the evolution in its use reflect a utilitarian and pragmatic view of criminal law. This article describes the evolution of the practice of corporate criminal liability and sentencing, arguing that administrative responses by the Department of Justice and the U.S. Sentencing Commission have responded to widespread criticism of the existence of corporate liability as well as the breadth of the respondeat superior standard of liability. As a result of this evolution in enforcement, only a very small number of corporations are convicted, and the penalties imposed on those that are convicted are adjusted to reflect corporate culpability. Nevertheless, the broad potential for criminal liability has significant consequences for a wide range of corporate behavior. Corporations have powerful incentives to perform internal investigations, cooperate with both regulators and prosecutors, and actively pursue settlement of claims of misconduct. To avoid criminal liability, corporations also enter into deferred prosecution agreements that often require changes in corporate business practices and governance as well as monitoring to ensure compliance. The purpose of these administrative responses attempt is to reduce or eliminate the negative effects of imposing criminal liability while exploiting the law’s power to deter criminal behavior, improve corporate citizenship, and bring about beneficial structural reforms. The persistence of the doctrine of respondeat-superior-based corporate criminal liability and its limitation in practice shed light on three key aspects federal criminal law. First, the Sentencing Guidelines have served as a more limited substitute for comprehensive criminal code reform. Second, the federal justice system lacks the resources to process the vast majority of cases falling under the criminal code, and prosecutorial discretion is relied upon to select a small fraction of cases for prosecution. Finally, like corporations, all defendants receive incentives for cooperation that may effectively compel them to plead guilty and/or assist in the investigation and prosecution of others